2010
DOI: 10.1186/1471-2164-11-606
|View full text |Cite
|
Sign up to set email alerts
|

Gene discovery from Jatropha curcas by sequencing of ESTs from normalized and full-length enriched cDNA library from developing seeds

Abstract: BackgroundJatropha curcas L. is promoted as an important non-edible biodiesel crop worldwide. Jatropha oil, which is a triacylglycerol, can be directly blended with petro-diesel or transesterified with methanol and used as biodiesel. Genetic improvement in jatropha is needed to increase the seed yield, oil content, drought and pest resistance, and to modify oil composition so that it becomes a technically and economically preferred source for biodiesel production. However, genetic improvement efforts in jatrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 58 publications
0
30
1
Order By: Relevance
“…4l). Contrary to earlier reports in J. curcas (Costa et al 2010;King et al 2011;Natarajan et al 2010;Jiang et al 2012;Xu et al 2011;Chen et al 2011) which focussed primarily on accumulation of oil, our results suggest a complex regulation of oil metabolism, possibly involving a delicate balance between diversion of carbon to lipid biosynthesis and catabolism of storage reserves to meet energy demands during seed maturation in J. curcas. For example, up regulation of transcripts for glyoxylate cycle specific enzymes like malate synthase and gluconeogenesis related enzymes like fructose 1, 6 bisphosphatase and phosphoenolpyruvate carboxykinase in JC3 suggests a possible breakdown of lipids for energy.…”
Section: Transcripts Related To Central Carbon Metabolismcontrasting
confidence: 99%
See 1 more Smart Citation
“…4l). Contrary to earlier reports in J. curcas (Costa et al 2010;King et al 2011;Natarajan et al 2010;Jiang et al 2012;Xu et al 2011;Chen et al 2011) which focussed primarily on accumulation of oil, our results suggest a complex regulation of oil metabolism, possibly involving a delicate balance between diversion of carbon to lipid biosynthesis and catabolism of storage reserves to meet energy demands during seed maturation in J. curcas. For example, up regulation of transcripts for glyoxylate cycle specific enzymes like malate synthase and gluconeogenesis related enzymes like fructose 1, 6 bisphosphatase and phosphoenolpyruvate carboxykinase in JC3 suggests a possible breakdown of lipids for energy.…”
Section: Transcripts Related To Central Carbon Metabolismcontrasting
confidence: 99%
“…In J. curcas, volumes of genomic data that include the whole genome (Sato et al 2011) and seed transcriptome information have been generated in the last few years (King et al 2011). A total of 12,084 expressed sequence tags (ESTs), from developing J. curcas seeds were sequenced and they represented genes coding for diverse biological functions (Natarajan et al 2010). Costa et al (2010) reported EST sequencing based identification of genes related to oil accumulation and degradation using developing and germinating seeds of J. curcas.…”
Section: Introductionmentioning
confidence: 99%
“…Natarajan et al have reported 12,084 ESTs using a normalized cDNA library from developing seeds (Natarajan et al 2010), and Costa et al have reported 13,249 ESTs using non-normalized cDNA libraries from developing and germinating endosperm (Costa et al 2010). In addition to these approaches using the conventional Sanger sequencing method, e orts have been made to accumulate transcriptome data for Jatropha by using a next-generation sequencer.…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptome, proteome and genome of Jatropha seeds have been analyzed to facilitate the understanding of the mechanisms of oil production (Yang et al, 2009;Natarajan et al, 2010;Jiang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%